Breech Presentation and Maternal and Perinatal Outcome in a Tertiary Care Teaching Hospital of Central Nepal - Acharya, Manisha; Kumar, Praveen; Shrestha, Rubina; Chhetri, Puja Baniya; Lamichhane, Mamata; Neupane, Srijana (Journal of College of Medical Sciences-Nepal, 2020)
Introduction: Breech is the commonest malpresentation. The objective of this study is to find out the prevalence of breech presentation at term. It also aims to present the mode of delivery conducted and to highlight the maternal and fetal complications associated with it. Methods: This was a descriptive cross-sectional study conducted in Department of Obstetrics and Gynaecology department of College of Medical Sciences done over a period of 2 years. All term pregnant women (≥ 37 weeks) aged 16 years and above, admitted to the maternity and labor ward with the diagnosis of singleton breech presentation during the study period were included in the study. Results: The incidence of breech presentation at term was 5.03%. Out of these, only 7 (18.92%) patients underwent breech vaginal delivery. Mean maternal age was 28.07 (± 11.56) years and majority were primigravidae. The mean birth weight of newborn was 2.8±0.5 kg. Conclusions: Breech presentation can result in both maternal and fetal complications. Skills related to conducting delivery in breech presentation must be learned by all those who manage pregnant women.